Strategi Pengelolaan Sampah di Kawasan Wisata : Literatur Review - Marthin Y. J. Dethan; Ishak I. Muda; Wilibaldus K. Nahak; Luh Putu Ruliati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Waste in tourist areas has become a complex environmental issue due to the increasing tourist activity that is not balanced with waste management capacity. This study aims to analyze various waste management strategies in tourist areas through a literature review approach. The research method follows the stages of Arksey & O'Malley (2005), which include identifying research questions, literature searches, article selection, data extraction, and synthesis of results. Literature sources came from the Google Scholar, ResearchGate, and Neliti databases, with the keywords